Statement of the Miners Federation of Great Britain, January 1927 (page 4)
1927-01-31 "Statement of the Miners Federation of Great Britain, January 1927 (page 4)" [g0495004.jpg], January 1927, Trades Union Congress Statement of the Miners Federation of Great Britain on the occasion of the conference of trade union executive committees held to receive the report of the General Council of the Trades Union Congress on the work entrusted to them in the General Strike of May 1926.